Direct, Indirect and Intermediary Relationship: Father Involvement, Early Intervention Program and Well-Being of Children with Special Needs - Mohamad Ilmee Mohamad Zin; Mariani Md Nor; Kama Shaffeei (Department of Special Education, 2018)
This research is led by the scenario that involve the fathers, early intervention programs and well-being of children with special needs. Therefore, this research was to examine whether the three constructs orvariables have direct, indirect and intermediary relationship (mediator) using Partial Least Squares Structural Equation Modelling (PLS-SEM). The samples are 158 fathers who have children with special needs aged 4 to 8.The results of this research prove that measurement of seven items in three constructs is significant and suitable for Well-being of Children with Special Needs (Child Health, and Child Housing and Environment); Early Intervention Program (Individual Family Service Plan, and Screening); and Father Involvement (Process Thought, Shared Interest, and Time). In conclusion, this research has proved the major findings, implications, and contribution to be used for future research.